Balancing organic carbon supply and consumption in the ocean's interior: Evidence from repeated biogeochemical observations conducted in the subarctic and subtropical western North Pacific. (8th May 2018) - Uchimiya, Mario; Fukuda, Hideki; Wakita, Masahide; Kitamura, Minoru; Kawakami, Hajime; Honda, Makio C.; Ogawa, Hiroshi; Nagata, Toshi
Abstract: The heterotrophic prokaryotic carbon demand (PCD) in the ocean's interior often substantially exceeds (by up to two orders of magnitude) the amount of organic carbon supplied by sinking particulate organic carbon (POC). A hypothesis to explain this carbon imbalance proposes that some non‐steady‐state processes have not been considered in previous studies based on snapshot data. To test this hypothesis, we collected time‐series (2.5 yr) data on sinking POC fluxes using moored sediment traps (trap deployment depths: 200 m, 500 m, and 4810 m) and compared them with the PCD data collected seasonally at two stations in the subarctic and subtropical western North Pacific. The POC supplies (ΔPOC) in the 200–500 m and 500–4810 m layers were estimated with a correction, when appropriate, for the non‐steady‐state effect arising from the change in the POC flux during the transit of POC between the upper and deeper traps. In the 200–500 m layer, ΔPOC generally exceeded or equaled PCD. In contrast, in the 500–4810 m layer, PCD generally exceeded ΔPOC by up to sevenfold. However, on a yearly basis, this carbon imbalance in the deeper layer decreased, with PCD balancing ΔPOC within a factor of 2. Therefore, the enigma of the high PCD relative to the POC flux in deep water is partially resolved by assuming a temporal uncoupling between supply and consumption, which partly equilibrates the carbon budget over a longer (yearly) time scale.